Comparison of Pethidine and Ketamine for the Treatment of Postoperative Shivering - Farooq, Muhammad Umar; Younis, Fazeela; Atif, Muhammad; Khan, Rao Ali Shan; Khalique, Abdul; Adnan, Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of Ketamine vs Pethidine for treating postoperative shivering in patients undergoing surgery under general anaesthesia.Study Design: Quasi-experimental study.Place and Duration of Study: Operation Theatre, Combined Military Hospital Sialkot Pakistan, from Jan to Apr 2020.Methodology: Following strict inclusion and exclusion criteria, patients who experienced postoperative shivering in the postanesthesia care unit (recovery) were enrolled through consecutive sampling and randomized into group-A or group B using the lottery method. Group-A received Pethidine 0.5 mg/kg and Group-B received Ketamine 0.2 mg/kg. The shivering grade was evaluated at 0 minutes and 5 minutes after administration of drugs by using a validated four-point scale.Results: Mean age of the patients was 34.12 ± 9.88 years and 34.83 ± 9.77 years in group-A and group B, respectively. At 5 min, the recovery rate of shivering was significantly higher in the Pethidine group than in the Ketamine group. In group-A, effecttiveness (grade 0) was noticed in 124 patients (86.2%) and in group-B effectiveness (grade-0) was seen in 74 patients (51.4%). A statistically significant difference (p